Checklist of Aphidiinae (Hymenoptera: Braconidae) and Aphelinus (Hymenoptera: Aphelinidae) species from Belgium with respectively four and three new records - Lopes, Thomas; Libert, Pierre-Nicolas; Starý, Petr; Japoshvili, George; Hatt, Séverin; Francis, Frédéric (Zootaxa, 2016)
Aphid parasitoids have good potential for crop protection. However, they have been poorly studied in Belgium, especially in terms of species diversity. Therefore, the aim of this work was to establish the first checklist for the country. To complete the list, aphid parasitoids were sampled in wheat and pea fields near Gembloux (Belgium), in 2013 and 2014. Among the identified species, Aphelinus asychis Walker, Aphelinus daucicola Kurdjumov, Aphelinus fusciscapus (Förster), Aphidius asteris Haliday, Aphidius eadyi Starý, Gonzalez & Hall, Praon barbatum Mackauer, and Trioxys auctus (Haliday) were recorded for the first time in Belgium. Thirty-two Aphidiinae and seven Aphelinus species were included in the checklist. It is hoped this study will stimulate further research, as species diversity is still low compared with neighbouring countries.